Mesoporous silica supported ytterbium as catalyst for synthesis of 1, 2‐disubstituted benzimidazoles and 2‐substituted benzimidazoles. (20th July 2018) - Samanta, Partha Kumar; Banerjee, Rumeli; Richards, Ryan M.; Biswas, Papu
Abstract : The benzimidazole ring is an important pharmacophore in contemporary drug discovery. Thus, effort to identifying new compounds containing benzimidazole scaffolds have gained much attention in recent years. In the present study, MCM‐41 type mesoporous silica with large pore ( l ‐MSN) supported ytterbium was successfully prepared by wet impregnation method. Among rare earth metal salts, ytterbium triflate has already been widely investigated as a catalyst in organic synthesis but less toxic ytterbium oxide has yet to be explored. Relatively high abundance and low cost of ytterbium with respect to many catalytically active metals (e.g. Pd, Au, Ru, Ir, Pt) offer an opportunity to develop sustainable catalysts for organic conversions. The catalyst has been characterized by various techniques including nitrogen adsorption, FT‐IR, TEM, SEM, EDX technique and elemental mapping. The obtained materials exhibit high surface area and a narrow distribution of mesoporosity. The catalytic performance of the Yb@ l –MSNs was tested by synthesis of 1, 2‐disubstituted benzimidazoles and 2‐substituted benzimidazoles through the coupling of aldehydes with o ‐phenylenediamine. The catalyst resulted in excellent yields in short reaction times and the reaction showed tolerance toward both electron‐donating and electron‐withdrawing functional groups at room temperature. A particularly interesting finding was the solvent selectivity of this reaction; namely, 1, 2‐disubstituted benzimidazoles generated as major product in water‐ethanol, while the 2‐substituted benzimidazoles was generated exclusively in non‐polar solvents like toluene. Abstract : Solvent selective synthesis of 1, 2‐disubstituted benzimidazoles and 2‐substituted benzimidazoles through the coupling of aldehydes with o ‐phenylenediamine has been reported utilizing mesoporous silica supported ytterbium as catalyst. 1, 2‐Disubstituted benzimidazoles generated as major product with more than 80% selectivity in water‐ethanol whereas the 2‐substituted benzimidazoles were generated exclusively in non‐polar solvents like toluene.